Tom Mouse - Le Guin, Ursula K., 1929-; Downing, Julie (Brookfield, Conn. : Roaring Brook Press, 2002)
Tom Mouse hides on the train he has boarded for travel and adventure, but an old woman finds and befriends him.
"A Neal Porter book"--T.p. verso.
Wilson's Children.
School Library Journal.
Pub Weekly.
4.9
K-3
Keywords: Mice -- Juvenile fiction; Mice -- Fiction; Railroads -- Trains -- Fiction; Travel -- Fiction; Friendship -- Fiction; Mice -- Fiction; Railroads -- Fiction; Travel -- Fiction; Friendship -- Fiction; Mice -- Fiction; Railroads -- Trains -- Fiction; Travel -- Fiction; Friendship -- Fiction